About one method of determining coil misalignments IN TOKAMAK - Vasiliy Rudakov; A. V. Georgiyevskiy (East European Journal of Physics, 2013)
The paper presents a highly sensitive “e-beam” method of determining misalignments of elements in the ITER-like magnetic system on the base of magnetic measurements. It is suggested to make a “tokamak-stellarator” hybrid by means of addition to the ITER-like magnetic system of a new, not helical Saw Tooth-shaped Coil1 (STC) in order to provide the creation of “resonance” magnetic surfaces with the angles of rotational transform t = n/m = 1/2 or t = 1/3. In one of variants the STC parts can be introduced into the vacuum vessel through the largest port and assembled into a single coil. The calculations of the ITER-like magnetic configuration show that due to the turn of the poloidal field coil PF3 around the axis X direction at an angle α = 1′ the resonance structure is formed with t = 1/2 and the maximum island width δ0≈50 mm. Under this tilt the maximum misalignment of coil elements from the design position Δα is only 3.5 mm. So, we have found the means for identification of misalignments in the case of magnetic system elements deviation from the design position to the values Δα » 1 mm that leads to the values of perturbing fields bj/B0 ≈ 3 10 –6.